Low muscle mass index is associated with type 2 diabetes risk in a Latin-American population: a cross-sectional study - Suárez, Rosario; Andrade, Celina; Bautista-Valarezo, Estefania; Sarmiento-Andrade, Yoredy; Matos, Andri; Jimenez, Oliver; Montalvan, Martha; Chapela, Sebastián (Frontiers in Nutrition, 2024)
Objective: Diabetes mellitus is a growing disease with severe complications. Various scores predict the risk of developing this pathology. The amount of muscle mass is associated with insulin resistance, yet there is no established evidence linking muscle mass with diabetes risk. This work aims to study that relationship.This cross-sectional study included 1388 employees. The FINDRISC score was used to assess type 2 diabetes risk, and bioimpedance was used for body composition analysis. Appendicular skeletal muscle mass adjusted by body mass index (ASM/BMI) was analyzed. Sociodemographic, clinical and anthropometric measures were evaluated, logistic regression models with sex stratification were conducted and ROC curves were calculated to determine the ability of ASM/BMI index to predict T2D risk.It was observed that patients with higher ASM/BMI had a lower FINDRISC score in both men and women (P < 0,001). A logistic regression model showed and association between ASM/BMI and diabetes risk in women [OR: 0,000 (0,000-0,900), p = 0,048], but not in men [OR: 0,267 (0,038-1,878) p = 0,185]. However, when the body mass index variable was excluded from the model, an association was found between muscle mass adjusted to BMI and diabetes risk in both men [OR: 0,000 (0,000-0,016), p < 0,001], and women [OR:0,001 (0,000-0,034) p < 0,001]. Other risk factors were having a low level of physical activity, waist circumference, age and sedentary lifestyle. A ROC curve was built and the optimal ASM/BMI cut-of value for predicting T2D risk was 0,82 with a sensitivity of 53,71% and specificity of 69,3% [AUC of 0,665 (0,64-0,69; P < 0,0001)] Conclusion: When quantifying the risk of type 2 diabetes in both women and men, assessing muscle mass can help detect adult individuals with a high risk of developing type 2 diabetes.